DO TAX SANCTIONS AFFECT TAXPAYER COMPLIANCE IN PAYING LAND AND BUILDING TAX? - Annisa, Tiara; Husnaini, Wahidatul (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.07.TAHUN.2025, 2025)
The research explores the relationship between taxpayer compliance with Land and Building Tax and factors such as tax understanding, awareness, and the presence of sanctions. Several previous studies have shown inconsistent results regarding how understanding, awareness, and tax penalties affect taxpayer compliance. The researchers used a quantitative approach by distributing questionnaires to 150 taxpayers in Mataram City and applied multiple linear regression to analyze the data and test the hypotheses. The study confirmed that taxpayer understanding and awareness affect compliance levels. Interestingly, tax sanctions did not affect people's willingness to pay Land and Building Taxes in Mataram City. The study’s findings imply that the government should enhance taxpayer understanding and awareness through effective education and awareness campaigns, as these factors significantly influence taxpayer compliance. Given that tax sanctions are ineffective, a shift towards more persuasive strategies is recommended. Simplifying payment processes and collaborating with local communities can further improve compliance rates, ultimately optimizing Land and Building Tax revenue and fostering public support for regional development.